Marisa Mosto. La búsqueda de la salvación. Ensayos filosóficos. Ediciones Sabiduría Cristiana, Buenos Aires, 2019, 208 p. - Cresta, Gerald (2018)
Fil: Cresta, Gerald. Universidad del Norte Santo Tomás de Aquino; Argentina